2019
DOI: 10.3390/jcm8091388
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Patterns in Stargardt Disease: Correlations with Visual Acuity and Disease Progression

Abstract: Background: To identify different choroidal patterns in Stargardt disease (STGD) and to assess their clinical correlates. Methods: 100 STGD eyes (29 males; mean age 42.6 ± 16.5 years) and 100 control eyes (29 males; mean age 43.2 ± 8.5 years) were included. Optical coherence tomography (OCT) and OCT angiography (OCTA) images were obtained. Four different choroidal patterns, quantitative OCT and OCTA parameters were assessed and statistically analyzed. The main outcome was the correlation between each choroidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 13 publications
(16 reference statements)
0
32
0
Order By: Relevance
“…These patterns positively correlated with loss of retinal structural integrity on OCT. Furthermore, only advanced patterns (ie, pattern 3 and pattern 4) showed remarkable signs of progression after one-year follow-up 76…”
Section: Monitoring Progression Of Stgd1mentioning
confidence: 96%
“…These patterns positively correlated with loss of retinal structural integrity on OCT. Furthermore, only advanced patterns (ie, pattern 3 and pattern 4) showed remarkable signs of progression after one-year follow-up 76…”
Section: Monitoring Progression Of Stgd1mentioning
confidence: 96%
“…Optical Coherence Tomography shows decreased thickness of the outer nuclear layer (ONL) and loss of external limiting membrane (ELM) and ellipsoid zone (EZ), all of which were shown to correlate well with VF defects (154,155). More recently, a novel imaging technique, optical coherence tomography angiography (OCTA), has been implemented to explore the existence and potential clinical relevance of different retinal and choroidal vascular patterns in RP patients (156,157).…”
Section: Gene Therapy In Retinitis Pigmentosamentioning
confidence: 99%
“…More recently, different STGD patterns have been described, characterized by progressively wider involvement of mid and extreme retinal periphery, as assessed by ultrawide field imaging (243). Furthermore, quantitative multimodal imaging and OCTA allowed to categorize STGD eyes accordingly to the amount of involvement of the retinal vascular and choroidal networks, highlighting different morpho-functional features and progression rates (156,244,245).…”
Section: Gene Therapy In Stargardt Diseasementioning
confidence: 99%
“…121 Adhi et al 217 also found that 64% of their STGD1 patients had an irregularly shaped choroidoscleral interface characterised by a concave-convex-concave appearance rather than the bowl-shaped contour in healthy controls. Arrigo et al 220 used OCTA to describe the progression of choroidal disease based on four patterns which are summarised in Table 7. Choroidal thinning has also been reported in RP 221,222 and cone dystrophy.…”
Section: Icga In Stgd1mentioning
confidence: 99%